Manajemen Hubungan Masyarakat dalam Meningkatkan Keterserapan Lulusan - Istighfarin, Clara Avilu; Imtiyaz, Adelia Retno; Felisa, Adinda Safa; Ilmi, Bahriatul; Zahra, Nadia Lailatuz; Wulandari, Ayu; Nuphanudin, Nuphanudin (TSAQOFAH, 2024)
The aim of this research is to find out to what extent community relations play a role in increasing the absorption of graduates at SMAN 1 Porong Sidoarjo and how to create students who are able to compete in the era of digital technology. The method used in this research is a qualitative method, a researcher goes directly to the location of the incident and directly interviews the informants of this research. From the results of this study, researchers realize the positive role of public relations management in guiding and transforming the delivery platform of students to universities and DU / DI as well as the positive role of utilizing public relations technology in creating creativity and innovation. The conclusion of the study is that SMAN 1 Porong has a good relationship with the community. SMAN 1 Porong also has policies that support the sustainability of public relations by establishing programs and strategies that link the development and achievement of college graduates who are able to realize your dreams. The Public Relations Department of SMAN 1 Porong also has its own role depending on its position. The role of technology in this school also helps students continue their learning to the next level. Students of SMAN 1 Porong also enjoy quite wide benefits in academic and non-academic fields, even at the national level.